2018
DOI: 10.1002/bjs5.50109
|View full text |Cite
|
Sign up to set email alerts
|

Radiological progression of end colostomy trephine diameter and area

Abstract: BackgroundDevelopment of a parastomal hernia is common following abdominoperineal excision (APE). The true incidence is difficult to assess fully owing to differing lengths of follow‐up and techniques used to assess herniation; radiological or clinical. The primary aim of this study was to evaluate colostomy diameter by studying the rate of change of axial and sagittal trephine diameters, trephine area, and the ratio of the trephine over time. A secondary aim was to investigate variation in trephine area and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
8
2
Order By: Relevance
“…Thus, the present simulations predict trephine enlargements that, on the average, are more pronounced for stomas located lateral to the RA muscle. This result is in apparent contradiction with the findings by Ho et al 2 , who found no statistically significant relation between the rate of trephine size progression and stoma position. Notwithstanding, these authors acknowledged as a limitation of their data analysis the fact that only 11.7% of patients had a stoma created lateral to the RA muscle.…”
Section: Trephine Enlargementcontrasting
confidence: 99%
“…Thus, the present simulations predict trephine enlargements that, on the average, are more pronounced for stomas located lateral to the RA muscle. This result is in apparent contradiction with the findings by Ho et al 2 , who found no statistically significant relation between the rate of trephine size progression and stoma position. Notwithstanding, these authors acknowledged as a limitation of their data analysis the fact that only 11.7% of patients had a stoma created lateral to the RA muscle.…”
Section: Trephine Enlargementcontrasting
confidence: 99%
“…Instrumentation, such as a template, that can help create an aperture less than 10 cm 2 or less than 50 mm in the largest dimension may reduce the frequency of PSH. Colostomy trephines increase over time [16], so the intraoperatively created aperture size should be significantly smaller than 10 cm2 or 50 mm in the largest dimension. Furthermore, prophylactic mesh placement may help reduce the frequency of PSH development when a relatively large abdominal wall defect at the colostomy site cannot be prevented, such as in patients with an ileus of the colon.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a stoma incision (trephine) of a diameter not larger than 25 mm was suggested under the assumption that PH were unlikely to develop for a small trephine provided that its size did not increase with time 16 . However, a more recent study showed that enlargement of the trephine, regardless of its original size, took place in almost every surveyed ostomy patient and that most patients developed PH even though the median trephine diameter of the patient cohort was below 25 mm 2 . Other surgical practices, such as an extraperitoneal exteriorization of the stoma (extraperitoneal tunneling of the stoma between the peritoneum and the AW) have been suggested for the prevention of PH.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most common complications of ostomies is the appearance of a parastomal hernia (PH) after the construction of the stoma. Even though PH is a very frequent problem (with reported incidences as high as 1 or 2 when identified by computed tomography) it is difficult to treat and has a huge impact on the quality of life of patients who suffer from it 3 6 . In recent years, there has been a striking interest in the prevention of PH with prosthetic meshes 7 13 .…”
Section: Introductionmentioning
confidence: 99%